Transformational Leadership Style and the Quality of Nursing Care in Riyadh Second Health Cluster, Saudi Arabia - Amira Y. Boshra; Juhayyir A. Almutairi; Sharifa M. Alasiry (Journal of Pharmacy and Bioallied Sciences)
Objective: This study aimed to determine the impact of a transformational leadership style on the quality of nursing care in the second health cluster of Riyadh, Saudi Arabia. Methods: A quantitative cross-sectional research design was used in this investigation. Convenience sampling was used to choose 350 nurses as participants for the investigation. The nurses’ perceptions of transformational leadership and the quality of nursing care were evaluated using the Global Transformational Leadership Scale and the Quality Nursing Care Scale. A 52-item online survey that participants self-administered through Google Forms was used to collect data. Results: The nurses perceived leadership positively and endorsed transformational qualities, with a mean value of 3.87 and a total score of 27.15. The Quality of Nursing Care Scale, which had a total score of 146.5 and a mean of 4.07, indicates nurses’ approval of the present quality of care and a holistic approach to patient well-being. Conclusion: A strong positive link was found between quality of nursing care and transformative leadership.